Mining in Minas Gerais: an analysis of its expansion and the environmental and social impacts caused by decades of exploration - Rezende, Vanessa Leite (Sociedade & Natureza, 2016)
The state of Minas Gerais has been suffering from the mineral exploration since inception of coloniza-tion in Brazil. Despite this, today is the state that has more mineral reserves, which creates an encounter between mineral production and environmental conservation, since the mineral extraction generates deforestation and other environmental impacts. The aim of this study was to obtain an overview of the expansion of mining and the resulting impacts of mining over the years in the state. The results showed that in recent decades there has been a large increase in the expansion of mines in the state, as well as environmental and public health impacts in cities that harbor the oldest mining. Thus, it was concluded that to be an important source of savings for Brazil, it becomes necessary to review the environmental policy of large mining and increase supervision by the public agency so that we can ensure the sources of mineral and quality environmental for future generations.